Islamic Green Banking Competitive Model: Strengthening Customer Loyalty in BPRS Mitra Mentari Sejahtera - Fatkhur Rohman Albanjari; Nugraheni Fitroh R. Syakarna; Syafiatul Makrifah Maysarah; Anisah Salma Ramadhani (Islamic Economics Journal, 2026)
Implementing green banking in Islamic credit banks (BPRS) is particularly challenging because these microfinance institutions operate with limited resources while simultaneously maintaining close social, religious, and community-based relationships with local customers. Environmental sustainability issues have encouraged the Islamic banking sector to integrate environmentally friendly principles into its operations through the concept of green banking. This study aims to analyze the implementation of green banking at BPRS Mitra Mentari Sejahtera and its effect on customer loyalty and competitive advantage. The research uses a mixed-methods sequential exploratory design, with a qualitative stage comprising in-depth interviews and Focus Group Discussions (FGDs), followed by the Analytic Network Process (ANP) to determine the priority factors in the decision network model. The participants included the Branch Manager, Funding Officers, Operational Managers, Islamic banking practitioners, and selected customers who were involved in banking services. The results show that green financing is the dominant factor in implementing green banking, while reputation is the main determinant of competitive advantage. In terms of customer loyalty, trust has the highest weight compared to satisfaction, commitment, and word of mouth. Priority analysis indicates that green banking contributes more strongly to competitive advantage than to customer loyalty directly, with reputation and green financing as the main drivers of competitiveness. Customer loyalty is formed indirectly by strengthening institutional reputation and customer trust. These findings confirm that green banking at BPRS is not merely an operational policy but rather a value-based institutional strategy that strengthens reputation and builds trust, the foundation of customer loyalty.